Rumen bacterial diversity in relation to nitrogen retention in beef cattle - Gomes Carvalho Alves, Kênia Larissa [UNESP]; Granja-Salcedo, Yury Tatiana [UNESP]; Messana, Juliana Duarte [UNESP]; Carneiro de Souza, Vinícius [UNESP]; Generoso Ganga, Maria Júlia [UNESP]; Detogni Colovate, Paulo Henrique [UNESP]; Kishi, Luciano Takeshi [UNESP]; Berchielli, Telma Teresinha [UNESP] (Elsevier, 2021)
This study aimed to characterize the rumen bacterial diversity of beef steers differing in the efficiency of nitrogen retention (ENR). Eight castrated steers and fitted with ruminal silicone - and duodenal T-type cannulas were used in a cross-over design with three consecutive periods and three diets. During each experimental period, nitrogen balance was measured, and based on the efficiency of N utilization data, steers were split into three ENR groups: high (HNR, 56.6% ± 3.3%, n = 10), medium (MNR, 45.8% ± 2.2%, n = 6), and low (LNR, 37.7% ± 1.9%, n = 8) using the NbClust package version 2.0.4 in R. Prevotellaceae, Lactobacillaceae, Leuconostocaceae, Clostridiales_Incertae_Sedis_XIII, Lachnospiraceae, and Peptostreptococcaceae were more abundant in LNR (P < 0.05) compared to HNR or MNR. Negative correlations were found between N retention and Mogibacterium, Anaerofustis, Butyrivibrio, Coprococcus, Hespellia, Lactonifactor and Lachnospiraceae (r ≤ −0.61; P ≤ 0.05). Prevotella, Hespellia, Lactonifactor, Lachnospiraceae_other, and Anaerobiospirillum were positively correlated between urinary N excretion (r > 0.55; P < 0.01), and negative correlations were found with Elusimicrobia, Victivallis and Treponema (r < −0.41; P < 0.05). The adjustment of the rumen bacterial community differed significantly between the N use retention groups. The high N retention in beef cattle was associated with less abundant bacteria in the rumen; however, N fixation capacity and uncharacterized rumen microorganisms need to be elucidated in future studies. In contrast, lower N utilization was associated with high abundance of bacteria that promote greater urinary N excretion through ruminal protein degradation.
Keywords: Cattle; Nitrogen utilization; Rumen microbiome; Urinary excretion